Pump Handbook (3rd Edition) - Karassik, Igor J. (McGraw-Hill Companies, 2011)
This book provides practical data and know-how on the design, application, specification, purchase, operation, troubleshooting, and maintenance of pumps of every type. It is an essential working tool for engineers in a wide variety of industries, all those who are pump specialists, in addition to those who need to acquaint themselves with pump technology.